Talk of the Devil : the collected writings of Ian Fleming - Fleming, Ian, 1908-1964 (William Morrow, an imprint of HarperCollins Publishers, 2025)
"A fascinating collection of rarely seen journalism, travel writing, short stories, and more by Ian Fleming, author of the James Bond series. Ian Fleming was best known for bringing to life the legendary character of James Bond, one of the most beloved and enduring icons of our time, but he was perhaps even more interesting than his creation. His career in naval intelligence and extensive travels around the world gave Fleming a keen eye and the authority to write on a wide range of topics beyond Bond's adventures. This collection contains a selection of journalism and other writings by Fleming, covering his wartime experiences, reflections on crime and espionage, and the process of writing his novels, among other topics. Readers will feel like they are right beside Fleming, immersed in his world as he works to meet the deadline for his next Bond novel, or participates in a mortifying golf tournament, or befriends an octopus in his beloved Jamaica. He was a man of the times, and these pieces encapsulate a bygone era through the lens of his observant gaze. A black-and-white photo section gives dimension to the man behind the myth, bringing life to his words and providing a unique glimpse into Fleming's world"--